Meningkatkan Keterampilan Membaca Siswa Dengan Penggunaan Media Kartu Kata Pada Pembelajaran Bahasa Indonesia Kelas III Di SD Negeri Batu Balian 3 Kabupaten Banjar - Irni Cahyani; Amelia Safitri (Journal of Humanities, Social Sciences, and Education, 2025)
Learning to read is the most important and fundamental aspect of education because it is only through reading that we can learn everything about school, society, and even the outside world that students often desire. However, many students at Batu Balian 3 Public Elementary School, particularly third graders, still lack reading skills. This is due to the monotonous learning process. This makes the learning process boring, and students quickly become bored with the lessons taught. Therefore, this study aims to determine the use of word cards and to improve the reading skills of third-grade students at Batu Balian 3 Public Elementary School, Banjar Regency. This study used a mixed-methods approach, focusing on descriptive qualitative data to determine the use of word cards and supported by quantitative data from test results to measure improvements in students' reading skills. Data were collected through direct observation and reading ability tests (pretest and posttest). The results of this study indicate that the use of word cards in improving the reading skills of third-grade students at Batu Balian 3 Public Elementary School, Banjar Regency, was implemented through several systematic stages. These stages include letter and syllable recognition, mastery of new vocabulary, and practice constructing sentences using the SPOK (Subject, Predicate, Object, Adverb) structure. Students take turns arranging word cards and reading them aloud in front of the class, making the learning process more interactive and focused. Quantitative test data showed a significant improvement in students' reading skills after implementing word cards. Further observations during the study confirmed that this medium was highly effective in improving students' reading skills. This is because word cards facilitate students' visual and auditory word recognition, enrich their vocabulary, and improve reading fluency. Furthermore, students' understanding of basic sentence structure also improved, positively impacting their ability to comprehend the overall content of the reading. Thus, word cards have proven to be an efficient and comprehensive tool for improving students' reading skills at Batu Balian 3 Elementary School, Banjar Regency.